PENGARUH STRUKTUR MODAL, SIZE, PROFITABILITAS, DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN - Anggraini, Kevin Yulia; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine empirically the influence of capital structure, size, profitability and ownership structure to the firm value. The population is manufacturing companies which are listed in Indonesia Stock Exchange in 2012-2015 periods. The samples are 21 companies companies which have been selected by purposive sampling. This research has been carried out by using multiple linear regressions analysis and classic assumption test. These result of the research indicates that size give positive influence to the firm value because company with a large size indicates the company has a high commitment, profitability give positive influence to the firm value because when the company has high level of profit, its firm value will be high. Capital structure does not give any influenceto the firm value, as investors tend to asset the company by taking into account profits. Managerial ownership does not give anyinfluence because of the small numbersof stocksthat are owned by the managerial will make so as decrease the firm value. The institutional ownership does give any influence because large number of stockholders is ineffective in monitoring the manager behavior in the company.Keywords: capital structure, size, profitability, ownership structure, firm value.